Management of gun shot injury in a tertiary hospital - Joshi, A (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Gun shot injury is an uncommon surgical emergency . A timely and multidisciplinary management by surgical team is an essential factor in decreasing mortality and morbidity . This study highlights the multidisciplinary management of gun shot injury.Methodology: Bir hospital is a postgraduate teaching hospital under National Academy of Medical Sciences and tertiary referral center in Kathmandu. A prospective cohort study of gunshot injury was conducted during Septemeber 2015 and early outcome analysis was done.Results: There were thirteen cases of gunshot wound. The mean age of casualty was 31 years and all were male.Injury                 Number (n)    Intervention                             Outcome Large intestine            3            Laparotomy                             Ileostomy/wound infection Perineum                   1            Exploration/Debridement           Loop ileostomy Bone- fracture            3            Traction/Enternal fixation/                                               Open reduction Internal Fixation Vertebra                     1                                                          Right hip power 3/5 Vascular- AV fistula      1           stenting                                   Referred Brachial plexus            1                                                         Sensory/motor deficit Neck                           2           Exploration                              Marginal mandibular                                                                                              nerve palsy Elbow                          1           Debridement/Split                                                thickness skin graftThere were no mortality and one case was referred.Discussion: With the multidisciplinary team approach, all the gunshot injury cases were managed with good outcome. The timely intervention by a surgical team is an essential factor for proper management of gun shot injury.